IoT-Based Gas Leak Detection Security System for Boarding House Environments: A Case Study of Kuning Ciumbuleuit Boarding House - Aqila, Angga; Hidayat, Hidayat; Maulina, Raisya; Ramadhani, Muhammad Wilyan; Dwisakti, Gilang (International Journal of Research and Applied Technology (INJURATECH), 2025)
Gas leaks from Liquefied Petroleum Gas (LPG) could be a severe issue that could result in fires and/or explosions, especially if the area is highly populated, as in the case of a dormitory. Furthermore, the absence of gas detecting system within the initial stages may turn out be deadly. In this regard, an Internet of Things (IoT) based gas sensor, NodeMCU ESP8266 as a data processor unit, and the Telegram app as a warning notification unit in the system. As soon as the gas content exceeds the safety limit within the ambient environment, the system automatically produces a warning notification alert on the user’s cellphone through Telegram app. Based on the experimental output, it has been identified that the system takes a total of 2 to 3 seconds to react after the gas has been identified. This efficient system has been found to provide effective gas leak detection at an optimum distance of not more than 15 cm from the sensor device. Additionally, two warning modes are employed to increase the awarness of the user. With such an easy setup and a lower cost, this system would be an excellent option to be employed within a dorm environment.